Menduga masa kadaluarsa mie basah ikan Patin (Pangasius hypophthalmus) dengan laju penurunan mutu model Q10 - H Hermansyah; Tyas Wara Sulistyaningrum; N Norhayani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2019)
The aim of this research are (1) to know the increased nutrition of wet noodle with the adding of pulverized Silver Catfish (Pangasius hypophthalmus) meat, (2) to presume the expiration date of wet noodle with the adding of pulverized silver catfish meat which stored in the refrigerator under 10°C temperature. This research used Completely Randomized Design (CRD) with 3 treatments which were Treatment A (The making process of wet noodle with the adding of 5% pulverized Silver Catfish from the weight of the wheat flour), B (The making process of wet noodle with the adding of 10% pulverized silver catfish from the weight of the wheat flour), C (The making process of wet noodle with the adding of 15% pulverized silver catfish from the weight of the wheat flour). The data were collected based on the result of the water content test and total of microbe test monitoring during the storage. Result of the research shown that the best water content was in the 10% treatment and the lowest of total bacterial colony that was tested using Total Plate Count (TPC) analysis was in the 15% treatment of Silver Catfish. The shelf life of wet noodle that being stored in 10°C was 7 days. Keywords : Expiration date assessment, wet noodle, Q10 quality model, Silver Catfish.